UPAYA MENINGKATKAN LAYANAN BIMBINGAN BELAJAR UNTUK MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK - Sukarlo Manik (Smart Education, 2020)
Abstract: The objectives of this study were: (1) To find out how to improve the learning activities of students in class VIII SMP Negeri 2 Sei Kepayang Kec. Sei Kepayang barat 2018/2019 academic year; (2) How big is the effect of tutoring on the learning activities of students in class VIII SMP Negeri 2 Sei Kepayang Kec. Sei Kepayang barat 2018/2019 academic year. The learning improvement procedure includes the implementation of classroom action research in 2 cycles. In the first cycle of the 6 categories observed in the tutoring service, only 2 were included in the